Prediction of Interaction and Stability of Bioactive Compounds from Acalypha indica L. with Acetylcholinesterase as Alzheimer’s Drug Candidates: A Docking and Molecular Dynamics Study - Lisa Savitri; Kharisul Ihsan; Rochmad Krissanjaya; Elfred Rinaldo Kasimo (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
Alzheimer’s disease remains one of the most challenging neurodegenerative disorders, with acetylcholinesterase (AChE) inhibition serving as a key therapeutic strategy. This study evaluated the interaction profiles and dynamic stability of bioactive compounds from Acalypha indica L. as potential AChE inhibitors using molecular docking and molecular dynamics simulations. Candidate compounds were screened for drug-likeness through SwissADME and toxicity predictions using ProTox-II. Docking results identified Compound A as the strongest binder, showing a favorable binding energy of -9.2 kcal/mol and forming stable interactions with catalytic and peripheral residues of AChE. A 100-ns molecular dynamics simulation demonstrated the stability of the protein-ligand complex, supported by consistent RMSD and radius of gyration values. Residue-level flexibility analysis revealed minimal fluctuations in the active site, and hydrogen-bond monitoring indicated persistent interactions throughout the simulation. MM-PBSA calculations yielded a binding free energy of -32.4 ± 3.1 kcal/mol, with van der Waals contributions dominating the interaction. These findings suggest that Compound A is a promising lead candidate for further experimental validation as an AChE inhibitor and may contribute to the development of new therapeutic agents for Alzheimer’s disease.